Acute severe hepatitis in children following extrahepatic infection in South Korea: etiology, clinical course, and outcomes - Sanghoon Lee; Young Ok Kim; Seo-Hee Kim (Acute and Critical Care)
Background Acute hepatitis can occur in association with systemic diseases outside the liver. Acute severe hepatitis with markedly elevated transaminase levels following extrahepatic infection has been reported in children. However, research on this condition remains limited. This study aimed to investigate its etiology, clinical course, and outcomes. Methods We retrospectively reviewed data from 2013 to 2020 for children under 12 years old with elevated liver enzymes following systemic infection. Acute severe hepatitis was defined as serum transaminase levels exceeding 1,000 IU/L in the absence of underlying liver disease. We analyzed hepatitis-associated pathogens, liver enzyme trends, and factors influencing recovery. Results A total of 39 patients were included in this study. The most common age group was 7–12 months (54.8%), and 53.8% were male. Respiratory infections were the most common (61.5%), followed by gastrointestinal infections (23.1%), meningitis (10.3%), and urinary tract infections (5.1%). The median peak alanine transaminase (ALT) level was 1,515.8±424.2 IU/L, with a median time to peak ALT of 4.4±2.3 days from symptom onset. ALT levels normalized within 21 days in 71.2% of patients and within 28 days in 94.9%. Younger age was associated with delayed ALT normalization, whereas hepatoprotective agent use was associated with faster normalization. Conclusions Acute severe hepatitis can develop following respiratory and other systemic infections. Younger children were more susceptible and had a more prolonged disease course.